Ngabuburit AI 2026: Pemberdayaan Pendidik melalui Pemanfaatan NotebookLM dalam Penyusunan Buku Ajar Sistematis - Interaktif - Eko Nursanty; Rizka Khairunnisa; Utomo; Marlianti (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
This community service program addressed the limited capacity of educators to use artificial intelligence in a structured and pedagogically responsible way for textbook development. The program focused on empowering educators through NotebookLM in the Ngabuburit AI 2026 activity. Its objective was to improve participants’ understanding and practical skills in organizing sources, designing textbook structures, developing chapter content, and generating interactive learning media. The program used a participatory training approach consisting of presentation, demonstration, guided practice, discussion, and feedback-based evaluation. The results showed that participants gained a clearer understanding of AI-assisted academic writing workflows and recognized NotebookLM as a useful tool for integrating source analysis, textbook writing, and learning media preparation. The activity also fostered new awareness that artificial intelligence can strengthen, rather than replace, educators’ academic roles in producing more systematic and interactive teaching materials.